Studi Literatur: Efektivitas Fitokimia Apigenin dalam Penurunan Tekanan Darah - Angelica, Neffa Syavella; Atmaka, Dominikus Raditya (Media Gizi Kesmas, 2025)
Background: High blood pressure or hypertension is a non-communicable disease, but it is one of the leading causes of death in the world. In 2023, the World Health Organization (WHO) stated that 46% adults   suffer from hypertension and most are unaware of it. One of the treatments for hypertension is to use non-pharmacological, namely apigenin-type flavonoids. Apigenin has antioxidant, anti-inflammatory, and anti-apoptosis activity so it has the potential to lower blood pressure with a decrease in oxidative stress. Objective: This study aims to examine the effectiveness of apigenin on blood pressure reduction based on existing literature. Methods: Secondary data were obtained from searching scientific articles through the PubMed and Science Direct databases within the last five years (2020-2024). After screening, four scientific articles met the criteria and could be used to continue this research. Result: The results of the literature review reported that apigenin is a type of flavonoids that lower blood pressure by preventing blood vessels from narrowing by reducing oxidative stress and inflammation. Apigenin is known to have a Pthalide element that can relax blood vessels, allowing blood output from the heart to be smooth and slowly blood pressure will return to normal. Apigenin is also known to help prevent kidney damage caused by low-fat diets. Studies also show that apigenin can increase nitrate oxidation, reduce oxidative stress, and reduce the risk of atherosclerosis. Conclusion: This review concluded that apigenin can be a non-pharmacological drug in lowering blood pressure by decreasing oxidative stress. In addition, apigenin can be antioxidant, anti-cancer, anti-inflammatory, and anti-bacterial. However, the right dose to lower blood pressure still needs further research.